Процес формування волоконних світловодів як об’єкт вивчення - Зінькевич, Олексій Петрович; Нещадим, Олександр Михайлович; Сафонов, Владимир Михайлович (My University, 2015)
В статті розглядається процес формування волоконних світловодів та вплив нестабільності зовнішніх умов на експлуатаційні характеристики готової продукції. This paper considers the process of forming fibers and the influence of instability of the external environment on the performance of the finished product. The basic methods of drawing of optical fibers, and the approach to the construction of rheological models of the formation zone are studied. The performance characteristics of the finished product fully depend on the effective functioning of automatic control systems for technological processes of drawing optical fibers (SC). For operational process control, it is necessary to know the stationary process of formation, as well as the recall of the process of instability of the external conditions of formation; it is necessary to know the values of the control parameters that contribute to obtaining products of the required quality. This can be done on the basis of the construction of an adequate mathematical model for drawing out the Armed Forces. В статье рассматривается процесс формирования волоконных световодов и влияние нестабильности внешних условий на эксплуатационные характеристики готовой продукции. Изучаются основные методы вытягивания волоконных световодов, та подход к построению реологических моделей зон формирования. Эксплуатационные характеристики готовой продукции в полной мере зависят от эффективного функционирования автоматических систем управления технологическими процессами вытяжки волоконных световодов (ВС). Для оперативного управления процессом необходимо знать стационарный процесс формирования, а также отзыв процесса нестабильности внешних условий формирования; необходимо знать те значения управляющих параметров, которые способствуют получению продукции требуемого качества. Сделать это можно на основе построения адекватной математической модели вытягивания ВС.
Keywords: кафедра вищої математики імені проф. Можара В. І.; волоконні світловоди; область прядомості; гідродинамічна стійкість; вільна поверхня; реологічна модель; зони формування; розрив; розпад на каплі; методи витягування; fiber optic; cable area predmosti; hydrodynamic stability; free surface; rheologicat model; the zone of the formation; dissolution; disintegration into droplets; methods of stretching